OPTIMIZING THE UNDERSTANDING OF FIQH MUAMALAH THROUGH COUNSELING ASSISTANCE FOR MOSQUE CONGREGATIONS IN GRESIK - Majduddin, Mohammad; Najib, Muhammad; Makinuddin, Mohammad; Syani Amrulloh, Friendis; Andleeb, Naima (SMARTINDO, 2025)
This study aims to evaluate the effectiveness of mosque congregant assistance in optimizing the understanding of fiqh muamalah in the Gresik Regency. The researcher employs a social action research design through in-depth interviews, participatory observation, and documentation of counseling activities. The findings indicate that continuous guidance through counseling significantly enhances congregants’ understanding of fundamental fiqh muamalah concepts, such as sales transactions, debt obligations, and zakat practices. Participants demonstrate increased comprehension and application of these principles daily, reflecting a deeper understanding of Islamic economic ethics. Although the results are positive, several challenges arise, including time constraints, limited access to easily comprehensible literature, and varying levels of participant motivation. This article recommends developing a more structured and inclusive counseling program using digital technology to support independent learning and expand accessibility. Therefore, collaboration between religious leaders, local governments, and Islamic educational institutions is essential to ensure the program’s sustainability and long-term impact. By integrating these strategies, fiqh muamalah can be a solid foundation for building a just and prosperous society in line with Islamic principles. This study provides valuable insights into community-based religious education and its role in promoting ethical economic practices